ANALYSIS OF LOCAL WISDOM VALUES AT THE SITU GEDE TASIKMALAYA TOURIST ATTRACTION - Nazwa Azizah Genuita; Zahra Izzatul Jannah; Salsabilla Pridasa; Aveny Septi Astriani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to analyze the local wisdom values contained in the Situ Gede Tasikmalaya tourist attraction. The research method involves collecting data through documentation studies. Local wisdom values were identified and analyzed using descriptive analysis methods. The research results show that Situ Gede Tasikmalaya is a place rich in local wisdom values, including social, cultural and economic aspects. These values reflect the cultural heritage of the local community and contribute to the sustainability and identity of the tourist area. An in-depth analysis of local wisdom values in these tourist attractions can provide better insight into how tourism management and promotion can maintain and respect local wisdom, while improving the tourist experience. The implications of these findings can be used as a basis for developing strategies and policies that support the preservation of local wisdom values in tourism development in Situ Gede Tasikmalaya.